Optimering av slutflöde i produktionslina : Produktion av bakaxelbryggor hos Scania Luleå - Wahlroos, Tobias (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
Scania operates in a rapidly changing industry. Technical innovations, environmental requirements and green fuels are just some of the factors that force the transport sector to constantly develop in step with the environment. This is also the case at Scania Luleå and is reflected in the production of rear axle housings to trucks and buses. To meet customer demand, trends as increased degree of digitization and automation as well as upgrading of machines can be seen. With the changing demand for specific products, continuous improvements are required in existing production and the design of new production lines. Thus, questions about production capacity and working conditions are raised. Lean production with its principles can be used to optimize production and increase production capacity. With a sociotechnical approach, the human aspect of work can be met. This thesis combines principles from lean production and sociotechnical theories to optimize the end flow in the production line of rear axle housings at Scania Luleå. This with the aim of optimizing production to reach requested capacity increase, and the goal of achieving good working conditions in the workstations of the end flow. Purpose and goals are fulfilled by answering the questions: How is the end flow balanced to provide more predictable production? How can the time needed for cooling and drying of rear axle housings be minimized, or become a non-problem? How can the need for transport in the end flow be minimized? How can completion with quality control, leakage testing and sequence packing be designed for an optimized end flow with good working conditions? What can a final solution proposal look like to achieve implementation? To answer the questions, the implementation of the assignment was based on Scania's investment process - Production Equipment Investment Process – combined with a general design process. With this, structured observations, unstructured interviews and discrete event simulation were used to for description and analysis of ...